Electronics Circuits and Systems : Design and Applications - Sohiful Anuar, Zainol Murad (Editor) (Penerbit UniMAP, 2018)
Books order can be made directly to UniMAP Press, Universiti Malaysia Perlis. (penerbitan@unimap.edu.my / 04 9775159)